History and archaeology of eastern India - Datta, Asok Kumar (New Delhi : Books & Books, 1998)
Contributed articles chiefly on archaeology and history, from prehistoric to early historic period.
Includes bibliographical references.
Keywords: Archaeology -- India; India -- Antiquities